Accountability and Transparency Finance Through ISAK 35 in the Organization Non-Profit - Himmatul Fitri; Samsul Hady; Lalu Hamdani Husnan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Organization non-profit based religious manage public funds sourced from from trust people, so that demand accountability and transparency high financial. ISAK 35 is established as standard presentation report finance organization non-profit in Indonesia, however its implementation in context organization religious Still not optimal. Research This aim analyze implementation of ISAK 35 as instrument accountability and transparency finance in the organization non-profit religious research​ use approach qualitative with design studies case at the mosque in the sub-district Selong, East Lombok Regency. Data collected through semi- structured interviews and analysis document finance, then analyzed use analysis thematic reflective. Research results show that practice recording and reporting finance Still dominated by simple cash recording and not yet fulfil component report finance as required in ISAK 35. Accountability finance more understood as moral and religious obligations, while transparency information finance Still limited and informal in nature. Research This confirm that spiritual values do not in a way automatic ensure realization accountability and transparency substantive financial statements. ISAK 35 has the potential become instrument strategic governance​ finance organization non-profit religious if implemented in a way contextual and supported by improvements capacity manager.